2016
DOI: 10.1055/s-0036-1593621
|View full text |Cite
|
Sign up to set email alerts
|

Complications Related to Implant Fixation of Patellar Fractures: Comparison of Ring Pins versus Bent K-Wires

Abstract: Patellar fractures are characterized by injuries to the extensor and typically require surgical fixation. Among the methods used for fixation, the most common is the modified AO tension-band wiring technique. However, using this technique, implant migration occurs due to the lack of connections between the K-wires and the tension-band wire, which causes irritation and reduces fracture stability. Recently, new methods for tension-band wiring have been developed in which tension bands lock the K-wires through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…For transverse (C1) and stellate (C2) fractures, previous studies have concluded that CSTB is superior to MKTB, mainly because of fewer occurrences of symptomatic hardware for CSTB fixation, despite comparable failure rates [12,13]. Likewise, in comparison of MKTB and RPTB fixation, one study showed that hardware-associated complications occurred at a decreased rate with RPTB fixation [14].…”
Section: Introductionmentioning
confidence: 99%
“…For transverse (C1) and stellate (C2) fractures, previous studies have concluded that CSTB is superior to MKTB, mainly because of fewer occurrences of symptomatic hardware for CSTB fixation, despite comparable failure rates [12,13]. Likewise, in comparison of MKTB and RPTB fixation, one study showed that hardware-associated complications occurred at a decreased rate with RPTB fixation [14].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Despite several technical modifications, management of operative patella fractures continues to be a challenge with poor functional outcomes and high reoperation rates. [ 1 , 11 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, about comminuted patellar fractures, there are few solid reduction sites of the patella for towel clamps, and the reduction of patellar fracture cannot be performed effectively. Hence, complications like bone malunion of the patella and incidence of traumatic knee arthritis are commonly reported [8, 9, 28].…”
Section: Discussionmentioning
confidence: 99%